Tinjauan Hukum Bagi Nasabah Atas Pemblokiran Rekening Secara Sepihak (Studi Putusan Nomor 112/Pdt.G/2022/Pn.Yyk) - Jeaneta Cahyaningsih; Yunita Pramesti Ardi Nurva; Fendi Setyawan; Firman Floranta Adonara (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
The purpose of this study is to determine the form of legal protection for customers against unilateral account blocking by banks based on the perspective of prudence and to determine the legal consequences of agreements between banks and customers regarding such legal actions. This type of research uses a normative juridical approach, which means that it examines and analyzes the relationship between one law and another by considering the starting point of the research analysis of laws and regulations, using a legislative and conceptual approach. The results of this study indicate that legal protection for customers can be achieved through transparency and credibility of information, implementation of the principle of bank secrecy, and optimization of the role of the Deposit Insurance Corporation (LPS), as stated in the Banking Law. In addition, banks must adhere to the implementation of the principle of prudence so that the implementation of legal protection for customers is realized properly, thereby maintaining customer trust. The legal consequence of this action is that the bank's actions fall under the category of unlawful acts, thereby obligating the bank to compensate the customer